Ornamental Fish Marketing Mix Strategy in Jatinegara Ornamental Fish Market - Rasyiq, Arkan Naufal; Suryana, Asep Agus Handaka; Andriani, Yuli; Maulina, Ine (Torani Journal of Fisheries and Marine Science, 2024)
This study aims to determine the characteristics of sellers and analyze the 7P marketing mix strategy applied in the Jatinegara Ornamental Fish Market. The research will be conducted from August 2023 to September 2023 at the Jatinegara Ornamental Fish Market, Jatinegara District, East Jakarta. The research method used is the case study method, with a sampling technique that is purposive sampling. The data analysis used is Descriptive Marketing Mix. The results of research on ornamental fish sellers have male characteristics with the domicile of Jatinegara District, age range 26-40 years with the majority of the last high school education / equivalent. Sellers in this market earn an average income per day of Rp 1,500,000 – Rp 2,000,000 with 4-6 years of sales experience. The results of marketing mix research applied to the Jatinegara Ornamental Fish Market can be seen from the 7P point of view, namely 1) The results of the marketing mix in products include product diversity and types of packaging for transporting ornamental fish, 2) The results of the marketing mix in prices include price variations and causes of price variations, 3) The results of the marketing mix carried out include sales locations that are narrow land and no parking space is available, 4) Physical evidence include product arrangement and product information on display, 5) The results of the marketing mix in people include informative seller attitudes, 6) Promotion includes promotional media, 7) The process includes payment methods and receipts.